Accessing resources new web service application patterns for a service-oriented world. - Lipton, Paul
Mae West said, "When choosing between two evils, I always like to try the one I've never tried before." But sometimes, when choosing between two equally appealing options, the best policy is to take both. WS-Resource Framework and WS-Transfer, two new specifications for accessing XML representations of resources through Web Services have been announced. Although it's not uncommon to find competing specifications and standards in the world of Web services, this time we shouldn't be forced to make an exclusive choice because WS-Resource Framework and WS-Transfer can serve complimentary roles.